Accurate Prophetic Hadith related to Jerusalem and Muslim attitudes in dealing with them - Al Sherman, Khaled (Jordan Journal of Islamic Studies, 2023)
The study aims to collect accurate prophetic Hadith evidences related to Jerusalem and to study the debated Hadith with respect to corrections, weakening or likehood according to narrators in their corrections; then identify the most significant events included in these Hadith; the most salient work guiding the Muslim to adopt. The study concluded to some results, the most important is that the number of prophesy Hadith evidences directly related to Jerusalem are eight. The most important events mentioned by these Hadith are the conquest of Jerusalem, visiting Jerusalem as a holy act, that Antichrist does not enter Jerusalem, the decadence of calphlism in the holy land, the desire of Muslim to own a land even if it was small to be connected to Jerusalem. The study showed that Hadith directed Muslims to pray in Jerusalem, to be related to it on the material and moral levels, to take care of the mosque such as providing oil lamps before the invention of modern equipment in case the Muslims were not able to pray in it as indicator as taking special consideration to the status of Jerusalem. These Hadith urged Muslims that the mosque must always be in hands of Muslims, and to maintain Sharia’ as a religion and a way of life for the Islamic nation to the end of time.